PEMODELAN PROFIL DINAS PENDIDIKAN KECAMATAN BRINGIN KABUPATEN SEMARANG DENGAN SISTEM INFORMASI GEOGRAFIS - Pujiono Pujiono Pujiono; Fahmi Amiq (Semantik, 2011)
The development of education sector at this time to get serious attention because of the development of education, have a very positive impact in improving morale and intelligence of this nation. One of the districts in Semarang that has the potential of good education is Bringin. Although the district is located on the side of Semarang district, but the district has good potential prospects. Presentation of information in Beringin at the moment still require development, this is because information about the location of education is still lacking. The information displayed only the name and type of school, while other information such as distance, transport and other infrastructure that support is not yet available. With a Geographic Information System (GIS), the presentation of information education in Beringin can be done through exposure in the form of digital data or information related to the geographical conditions of a region. It aims to further develop a more reliable information so as to provide ease of both service-related education. The accuracy of information in Beringin that is related to the existence of an educational destination in a region will be very necessary to be a guideline of the agency concerned.Keyword : education information, digital information, GIS